Adolescent development and risk for the onset of social-emotional disorders: A review and conceptual model. (December 2019) - Rapee, Ronald M.; Oar, Ella L.; Johnco, Carly J.; Forbes, Miriam K.; Fardouly, Jasmine; Magson, Natasha R.; Richardson, Cele E.
Abstract: The adolescent developmental stage appears to be a sensitive period for the onset of several particular forms of mental disorder that are characterised by heightened emotionality and social sensitivity and are more common in females than males. We refer to these disorders (social anxiety disorder, generalised anxiety disorder, eating disorders, major depression) collectively as the social-emotional disorders. The aim of this paper is to address an important question in the understanding of social-emotional disorders – why do these disorders commonly begin during adolescence? We present a conceptual model that describes some of the key changes that occur during adolescence and that addresses some hypothesised ways in which these changes might increase risk for the development of social-emotional disorders. An overview of the extant empirical literature and some possible directions for future research are suggested. The model points to interesting links between psycho-social risk factors that should highlight potentially fruitful directions for both psychopathology research and early intervention programs. Highlights: Adolescence is a sensitive period for development of several mental disorders. These social-emotional disorders, include social and generalised anxieties, major depression, and eating disorders We propose that developmental changes during adolescence increase risk for onset of these disorders. Risks include pubertal changes and changes in emotion, sleep, self-concept, and peer relationships. Interactions between pre-adolescent risk and adolescent developmental changes likely triggers onset of disorder.